Microstructure and mechanical properties evolution of the Cr coatings on SiC substrates under He irradiation - Shuxin Dai; Zhanfeng Yan; Kun Liang; Peng Li; Fanping Meng; Ping Yu; Bingsheng Li; Fangfang Ge (Journal of Materials Research and Technology, 2024)
Environment coatings are frequently considered, to improve the corrosion resistance of silicon carbide (SiC) in pressurized water reactor (PWR) and boiling water reactor (BWR) surroundings. Chromium (Cr) is one of the main candidate materials for coatings on zirconium-based alloys for accident-tolerant fuel (AFT) cladding. In this work, the magnetron sputtered Cr coatings on SiC substrates were irradiated by the 500 keV He+ ions at room temperature. Moreover, the microstructural characterization was conducted on the irradiated specimens by using scanning electron microscope (SEM), and transmission electron microscope (TEM). The scratch test showed that the coating-substrate adhesion decreased from 41 N to 28 N (∼31.7%) before and after the irradiation, maybe due to that the irradiation produced tensile strain in the coating and mesophase along the coating-substrate interface. It revealed that irradiation accelerated the migration and aggregation of C elements on the surface of the coating. After the 800 °C annealing for 20 min, massive Cr atoms diffused into the SiC matrix and reacted with Cr to form a chromium silicide interlayer. Some cracks were observed at the interface, being attributed to the Kirkendall effect. Therefore, it is very necessary to avoid the formation of chromium silicide interlayer and decrease swelling mismatch between the metal coatings and the SiC substrate for the actual application in nuclear systems.